ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF DALAM MENDUKUNG PEMBELAJARAN BIOLOGI DI SMA NEGERI 18 MEDAN - Cindi Claudia Sipayung; Elza Amanda; Regina Anastasia Br.Gultom; Rosa Sari Amalia Nasution; Widya Arwita; Rizal Mukra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research is to analyze the needs for interactive multimedia-based learning media to support Biology learning at SMA Negeri 18 Medan. Biology learning often faces challenges due to abstract and complex concepts such as genetics and physiological systems, which are difficult for students to visualize using conventional media. This study employs a descriptive qualitative approach. Data were collected through semi-structured interviews with Biology teachers, utilizing an instrument that covers three main aspects: the implementation of learning models, the use of learning media, and learning constraints. The collected data were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The results indicate that Biology learning at SMA Negeri 18 Medan still relies heavily on printed books and static media, while the use of complex digital media remains suboptimal due to technical issues and time constraints. Students face significant difficulties in understanding microscopic and dynamic concepts, leading to uneven engagement. The findings highlight an urgent need for interactive multimedia that integrates 3D visualization, virtual laboratories, and gamification to bridge the gap between abstract concepts and concrete understanding, accommodate diverse learning styles, and increase student motivation and participation.